Analisis Pengaruh IsIR, ZPR, FDR dan PBH terhadap ROA Bank Umum Syariah di Indonesia - Rasyid Hardayansyah; Radia Purbayati; Rosma Pakpahan; Fatmi Hadiani (Journal of Applied Islamic Economics and Finance, 2023)
The development of Islamic Commercial Banks in Indonesia is very rapid when viewed from the ROA contained in the financial statements. The increase in ROA should also be followed by an increase in Islamic Income, Zakat, FDR and PBH. However, there are several problems that are required to conduct this research. The focus of this research is to see whether there is an influence between the independent variables on ROA. The type of research used is descriptive quantitative analysis. The type of data used is panel data and the data source comes from the annual financial statements and the research sample is 5 Islamic banks. Data collection techniques using documentation, literature study and literature. Data processing using EViews 10. The results showed that IsIR, FDR and Profit Sharing Financing had no effect on ROA because the p value > 0.05. ZPR has a positive and significant effect on ROA because p < 0.05.